The Fujimori legacy the rise of electoral authoritarianism in Peru - Carrión, Julio F.; Carrión, Julio F. (Penn State University Press, 2006)
President Alberto Fujimori's sudden resignation in November 2000 brought an end to a highly controversial period in Peruvian history. His meteoric rise to power in 1990 fueled by widespread popular support, followed by his decision to dissolve Congress and rule by decree in 1992, has made his regime a focus of special attention by scholars trying to understand this complex and contradictory presidency.This book offers a comprehensive assessment of Fujimori's regime in the context of Latin America's struggle to consolidate democracy after years of authoritarian rule. Setting the regime conceptually in a discussion of alternative forms of government-delegative democracy, neopopulism, and electoral authoritarianism-the essays study it from two different perspectives: external (in its relations with political parties, Lima's mayors, public opinion, women, the U.S. government) and internal (examining economic policies as determined by governing coalitions, networks of corruption, and Fujimori's unsavory relationship with his security advisor Vladimiro Montesinos). Overall, The Fujimori Legacy helps illuminate the persistent obstacles that Latin American countries face in establishing democracy.In addition to the editor, contributors are Robert Barr, Maxwell Cameron, Catherine Conaghan, Henry Dietz, Philip Mauceri, Cynthia McClintock, David Scott Palmer, Kenneth Roberts, Gregory Schmidt, John Sheahan, Kurt Weyland, and Carol Wise